Coupling coordination measurement and spatiotemporal evolution characteristics of digital economy, environmental regulation, and carbon emission intensity—Empirical evidence from Chinese provinces - Tang, Shibo (Frontiers in Environmental Economics, 2024)
Digital economy, as an innovative digital technology, can promote environmental governance and support low-carbon development. Under the backdrop of China's dual carbon strategy, the country faces significant challenges in achieving coordinated development across the domains of economy, environment, and energy. Based on panel data from 30 Chinese provinces between 2012 and 2022, this paper constructs a coupling coordination model to measure the level of integrated development among digital economy, environmental regulation, and carbon emission intensity. The study also examines the spatiotemporal evolution of this coordination using kernel density estimation and spatial correlation tests. Furthermore, empirical analysis via regression models was employed to investigate key influencing factors. The findings suggest that: (1) The coupling coordination level has shown an upward trend over the sample period, with no extreme regional disparities; (2) Spatially, the development of coupling coordination exhibits “high-high” and “low-low” clustering effects; (3) Development levels are influenced by various external driving factors, with significant regional differences in primary influencing factors. For these findings, the following recommendations are proposed: enhance digital infrastructure, optimize regulatory frameworks, and promote the integration of digital economy with green and low-carbon development.